2013
DOI: 10.1139/cjfas-2013-0150
|View full text |Cite
|
Sign up to set email alerts
|

Foraging efficiency and prey selectivity in a visual predator: differential effects of turbid and humic water

Abstract: Predators exert strong regulating forces on lower trophic levels through predation. As most fish are visual foragers, visual conditions in the water may alter the strength of this regulation. We evaluated effects of turbidity and humic water on foraging efficiency and prey-size selectivity in Northern pike (Esox lucius) feeding on roach (Rutilus rutilus). Encounter rates decreased in both turbid and humic water but were not counteracted by increased searching activity. Capture success was unaffected by turbidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
34
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 35 publications
4
34
0
Order By: Relevance
“…Positive effects of chlorophyll‐ a on prey fishes have also been found earlier (Mehner, ). The positive effect of turbidity on benthivorous cyprinids may be additionally explained by improved avoidance of visually hunting predators (Jönsson et al., ). Cyprinids also enjoy a competitive advantage over perch in turbid conditions (Diehl, ).…”
Section: Discussionmentioning
confidence: 99%
“…Positive effects of chlorophyll‐ a on prey fishes have also been found earlier (Mehner, ). The positive effect of turbidity on benthivorous cyprinids may be additionally explained by improved avoidance of visually hunting predators (Jönsson et al., ). Cyprinids also enjoy a competitive advantage over perch in turbid conditions (Diehl, ).…”
Section: Discussionmentioning
confidence: 99%
“…Another effect of brownification is that it may impact visually hunting predators, such as fish, making them less efficient predators, or forcing them to switch to larger, more easily detectable prey (i.e. Jönsson et al ., ), which may lead to changed prey (e.g. insect) community composition.…”
Section: Introductionmentioning
confidence: 99%
“…The two study lakes differ greatly in light transmission and the difference in the amount and the spectral distribution of the downward light is dramatic at depths of a few meters (Figure ). Earlier studies have shown that the foraging efficiency of fish decreases with increasing humic content (Jönsson et al ., ; Ranåker et al ., , ). Consequently, there should be a strong selection pressure for visual adaptations to the prevailing photic conditions.…”
Section: Discussionmentioning
confidence: 98%
“…An obvious advantage of increased contrast sensitivity is increased visual range, allowing, for example, a predator in turbid water to see its prey at a distance where it is itself still undetectable by the prey (or vice versa). Data such as presented here may allow modelling of complex detection, selection, escape and strike distance relations between species in different light environments (Jönsson et al ., , , ; Ranåker et al ., , ). For example, changes in relative predator–prey detection distances in changing light conditions may explain the differences in selectivity in S. lucioperca when foraging on P. fluviatilis and R. rutilus during day and night conditions and in waters with different humic content (Ranåker et al .…”
Section: Discussionmentioning
confidence: 99%